Identifying enablers and barriers to the implementation of the green infrastructure for urban flood management: a comparative analysis of the UK and China - Li, Lei; Collins, Alexandra M.; Cheshmehzangi, Ali; Chan, Faith Ka Shun (Elsevier, 2020)
Climate change and urbanization are increasing the urban flood risk, which can cause adverse on socio-economic and environmental impacts. Green Infrastructure (GI) can reduce stormwater runoff and offer multiple benefits that have been initiated in the United Kingdom (UK) and China, namely Sustainable Urban Drainage Systems (SUDS) and Sponge Cities Program (SCP) respectively. Currently, the implementation of GI is restricted to small spatial (site specific) scale and facing several constraints such as financial investment and governance, that limited its fuller functions and potential. This study aims to identify the barriers and enablers for the adoption of GI by investigating SUDS and SCP in the UK and China, through twelve in-depth semi-structured interviews with stakeholders. Our results found that multiple benefits of the SUDS and SCP were identified, as the main enablers in both countries with reducing the stormwater runoff and alleviating peak discharge in the drainage system, also contributing to social well-being and climate adaptations. Some barriers found the current practices are facing challenges from financial, biophysical and socio-political circumstances in both cases. We conclude that it is beneficial to learn the comparative findings and experiences from both countries, which contributes to stakeholders for improving current GI practices, in prior to achieve more sustainable long-term deliverables.